2022
DOI: 10.1007/s11306-021-01864-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling reveals a connection between aldehyde dehydrogenase 1A3 and GABA metabolism in breast cancer metastasis

Abstract: Introduction Aldehyde dehydrogenase 1A3 (ALDH1A3) is a cancer stem cell (CSC) marker and in breast cancer it is associated with triple-negative/basal-like subtypes and aggressive disease. Studies on the mechanisms of ALDH1A3 in cancer have primarily focused on gene expression changes induced by the enzyme; however, its effects on metabolism have thus far been unstudied and may reveal novel mechanisms of pathogenesis. Objective Determine how ALDH1A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Combination with neoadjuvant chemotherapy is also being Fig. 2 Neurotransmitter signaling pathways in breast cancer metastasis [8,45,55,61,93,95,[97][98][99][100]119]. Neurotransmitters such as acetylcholine (Ach), GABA, serotonin (5 HT), norepinephrine (NE), neuropeptide Y (NPY), and neurotensin (NTS) affect cancer progression through multiple signaling pathways.…”
Section: Beta Blockadementioning
confidence: 99%
See 2 more Smart Citations
“…Combination with neoadjuvant chemotherapy is also being Fig. 2 Neurotransmitter signaling pathways in breast cancer metastasis [8,45,55,61,93,95,[97][98][99][100]119]. Neurotransmitters such as acetylcholine (Ach), GABA, serotonin (5 HT), norepinephrine (NE), neuropeptide Y (NPY), and neurotensin (NTS) affect cancer progression through multiple signaling pathways.…”
Section: Beta Blockadementioning
confidence: 99%
“…Both Neman et al and Dahn et al have found that activation of GABA A receptors increase brain metastases in breast cancer patients. The receptor could therefore represent a promising therapeutic target [ 94 , 95 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, GABRP silencing decreased the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) [33]. Furthermore, GABA enhances the function of aldehyde dehydrogenase (ALDH)1A3, a cancer stem cell (CSC) marker in TNBC [34]. In mice harboring MDA-MB-231 tumors overexpressing ALDH1A3, GABA treatment increased breast cancer metastasis [34].…”
Section: Innervation Differs In Breast Cancer Subtypesmentioning
confidence: 99%
“…This may induce resistance of tumor cells to certain antimetabolite chemotherapy drugs such as D-2-deoxyglucose (121). Chen et al (122) found that breast cancer cells that metastasize to the brain have greater tolerance to low sugar levels than their parent cells; they also express more glutamate dehydrogenase and a-ketoacid dehydrogenase to use the glutamic acid and branched-chain amino acids available in the environment.…”
Section: Characteristics Of Tumor Cell Metabolism In the Microenviron...mentioning
confidence: 99%